OBSERVATIONAL RESULT ON COSMIC OBJECTS "Okean7" (94-08-1), "Sich-1" (95-132-1) - Dobrovolsky, A. V.; Paltsev, N. G.; Medvedev, Yu. A.; Shumilov, Yu. P.; Petrov, M. P.; Chaichuk, R. A.; Depenchuk, E. A.; Golubovskaya, T. A.; Strahova, S. L. (Одеські астрономічні публікації, 2017)
The results are represented of photometric observations of cosmic objects "Okean-7", "Sich-1", obtained at the Odessa Astronomical Observatory in September-October 1995.